Safety and efficacy of antibiotics compared with appendicectomy for treatment of uncomplicated acute appendicitis: meta-analysis of randomised controlled trials - Varadhan, Krishna K.; Neal, Keith R.; Lobo, Dileep N. (British Medical Association, 2012)
Objective To compare the safety and efficacy of antibiotic treatment versus appendicectomy for the primary treatment of uncomplicated acute appendicitis.